2014
DOI: 10.1016/j.jssc.2014.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of LaO1−xFxBiS2 (x~0.23, 0.46): Effect of F doping on distortion of Bi–S plane

Abstract: The crystal structures of superconducting LaO 1-x F x BiS 2 (x ~ 0.23, 0.46) were determined by single-crystal X-ray diffraction analysis. Their space group was P4/nmm.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 28 publications
11
78
0
Order By: Relevance
“…1(b). The density of the dark spots is about 3% per Bi atom, which is consistent with the results of the recent single-crystal X-ray diffraction measurements 43 . Besides the atomic defects, slightly dark streaks run along approximately diagonal directions of the unit cell.…”
supporting
confidence: 91%
“…1(b). The density of the dark spots is about 3% per Bi atom, which is consistent with the results of the recent single-crystal X-ray diffraction measurements 43 . Besides the atomic defects, slightly dark streaks run along approximately diagonal directions of the unit cell.…”
supporting
confidence: 91%
“…where RBi is an ionic radius of Bi ion. In this study, the ionic radius of Bi ion was obtained from the 89 structural data of the LaO0.77F0.23BiS2 single crystal [26]. Thus, the value of RBi was 104.75 pm, which is 90 the almost same value as that in the previous report [18].…”
supporting
confidence: 52%
“…15,16) Recently, crystal structure analysis using LaO 1-x F x BiS 2 single crystals has revealed that the distortion of the Bi-S plane disappears with increasing F concentration. 17) On the basis of these previous reports, we assume that the atomic position of the in-plane S site can be optimized by HP annealing, which results in an increase in T c in HP-annealed PrO 0.5 F 0.5 BiS 2 .…”
mentioning
confidence: 96%